Protonation of Imino Moiety in Aminoguanidine by Heterolytic O–H Bond Cleavage on Phthalic Acid: Theoretical, Experimental and DNA Binding Studies - Rajasekar, L.; Rajesh, R.; Dileep, D.; Pradeep, R.; Sivasankar, B.N. (Asian Journal of Chemistry, 2023)
Aqueous neutralization reaction between aminoguanidine hydrogencarbonate and phthalic acid yielded the crystals of aminoguanidine hydrogenphthalate monohydrate (AHPMH). The crystal quality is further improved by repeated recrystallization and single crystals were obtained. The single crystal XRD data reveals that the compound crystallizes in the monoclinic crystal system with the Cc space group. The unit cell consists of four molecules (z = 4) and in the crystal lattice they are linked by O–H···O and N–H···O intermolecular hydrogen bonding. Geometrical and vibrational analyses were performed by B3LYP/6311G(d,p) basis set and compared with the single crystal XRD values. The Mulliken charge and molecular electrostatic potential (MEP) analyses have been used to predict the reaction behaviour and bond cleavage fashion during the reaction. The heterolytic O-H bonding electrons are shifted towards the oxygen atom (-0.6112 e) and it possesses high electronegative which influenced the formation of strong hydrogen bond. The binding constant (Kb) of the AHPMH indicates that strong interactions are developed between the title compound and CT-DNA.